2016
DOI: 10.1186/s10152-016-0477-4
|View full text |Cite
|
Sign up to set email alerts
|

Modelling present and future global distributions of razor clams (Bivalvia: Solenidae)

Abstract: Razor clams (Pharidae and Solenidae) are deep-burrowing bivalves that inhabit shallow waters of the tropical, subtropical, and temperate seas. Using 'maximum entropy' , a species distribution modelling software, we predicted the most suitable environments for the entire family and 14 Solen species to indicate their present and future geographic distributions. Distance to land, depth, and sea surface temperature (SST) were the most important environmental variables in training and creating the present and futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 42 publications
4
26
0
1
Order By: Relevance
“…In addition, while species distribution models can predict species ranges (e.g. refs 58 , 63 ), they may not be appropriate for determining biogeographic realms and boundaries 49 . Our preliminary analysis of modeled species ranges from AquaMaps 64 returned patterns mirroring the environmental variables used to generate the models rather than patterns of endemicity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while species distribution models can predict species ranges (e.g. refs 58 , 63 ), they may not be appropriate for determining biogeographic realms and boundaries 49 . Our preliminary analysis of modeled species ranges from AquaMaps 64 returned patterns mirroring the environmental variables used to generate the models rather than patterns of endemicity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies have utilized open-access marine species distribution records to discover and confirm large-scale biodiversity patterns. These findings include observations that global species richness is bimodal with latitude, and that species richness decreases with depth (Chaudhary et al 2016a;Chaudhary et al 2017;Costello & Chaudhary 2017a;Saeedi et al 2017a;Saeedi & Costello 2019a;Saeedi & Costello 2019b;Saeedi et al 2017b). We conclude that there has been noticeable progress towards achieving the potential of Aichi Target 19 through establishing global databases and taxonomic resources.…”
Section: Reviewed Prioritiesmentioning
confidence: 58%
“…The distribution and diversity of deep-sea fauna thus still remains poorly-known due to the size and remoteness of deep-sea ecosystems. For example, recent studies have shown that the global latitudinal marine species richness gradient follows a bi-modal pattern related to temperature and habitat availability (Chaudhary et al 2016a;Chaudhary et al 2017;Saeedi et al 2017a;Saeedi & Costello 2019a;Saeedi & Costello 2019b;Saeedi et al 2017b). This finding is supported by the fossil record, which shows reduced species richness at the equator in warm periods (Kiessling & Aberhan 2007).…”
Section: Identifying Biodiversity and Biogeographic Knowledge Gaps Anmentioning
confidence: 86%
See 1 more Smart Citation
“…Examples of poor awareness of the uncertainties in climate data were also found. There were cases in which basic information regarding the number of and name(s) of the ESM(s) used in the study were unreported (Joo et al 2015 ; Seebens et al 2016 ), and one article which also failed to report the emission scenario used (Saeedi et al 2016 ). Each of these studies also failed to discuss how the climate data used to represent future conditions may have affected the ecological results they present.…”
Section: Literature Reviewmentioning
confidence: 99%